2022
DOI: 10.1021/acsami.1c18223
|View full text |Cite
|
Sign up to set email alerts
|

Silanization of Plasma-Activated Hexamethyldisiloxane-Based Plasma Polymers for Substrate-Independent Deposition of Coatings with Controlled Surface Chemistry

Abstract: Plasma polymerization has emerged as an appealing technique for surface modification because of its advantages over a variety of conventional techniques, including ease-of-use and the possibility to modify nearly any substrate. One of the main challenges of plasma polymer-based surface modification, however, is having control over the coating chemistry, as plasma deposition generates a diversity of chemical structures. Therefore, this study presents an alternative plasma-based method for the fabrication of coa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
21
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(22 citation statements)
references
References 65 publications
1
21
0
Order By: Relevance
“…The XPS spectrum of the PDMS exhibited a O1s/C1s photoemissions ratio of 1.09, while for the PDMS-RLs the ratio determined was 0.48, which indicates that the functionalization with RLs changed the PDMS surface chemical compositions by introducing more carbon. After curve-fitting, it can be observed that the high-resolution C1s XPS spectra of the PDMS exhibited four peaks, two well defined at 284.8 eV (C-Si/C-C/ C-H) and 285.5 eV (C-OH), and one small peak at 286.6 eV (C-O/C-N) [41,42]. However, in the C 1 s core-level spectrum of the PDMS-RLs surface (Fig.…”
Section: Xps and Ftir-atrmentioning
confidence: 99%
“…The XPS spectrum of the PDMS exhibited a O1s/C1s photoemissions ratio of 1.09, while for the PDMS-RLs the ratio determined was 0.48, which indicates that the functionalization with RLs changed the PDMS surface chemical compositions by introducing more carbon. After curve-fitting, it can be observed that the high-resolution C1s XPS spectra of the PDMS exhibited four peaks, two well defined at 284.8 eV (C-Si/C-C/ C-H) and 285.5 eV (C-OH), and one small peak at 286.6 eV (C-O/C-N) [41,42]. However, in the C 1 s core-level spectrum of the PDMS-RLs surface (Fig.…”
Section: Xps and Ftir-atrmentioning
confidence: 99%
“…Coatings produced from the plasma polymerization of siloxanes and perfluoro monomers are the main focus of this study. Plasma polymerized silanes, siloxanes, and silazanes coatings have been of interest to plasma polymer chemists for many years [ 32 , 33 , 34 , 35 , 36 ]. They offer convenient thin-film alternatives to conventional polysiloxanes, such as silicone rubber, which are versatile polymers and find vast applications in biomedical engineering, electrical engineering, aerospace engineering, automotive applications, O-rings, and many other fields [ 37 ] but are difficult to deposit as thin films.…”
Section: Introductionmentioning
confidence: 99%
“…In the last decades, plasma polymerization emerged as an attractive technique for surface modification because of its advantages over a variety of conventional techniques. [1][2] Usually, plasma polymerization refers to the deposition of cross-linked, sub-micrometer coatings by introducing organic compounds (often called precursors or monomers) in a non-thermal plasma. [3][4] A variety of different types of plasma polymerization exist, among which plasma-enhanced chemical vapor deposition (PECVD) is the most investigated type.…”
Section: Introductionmentioning
confidence: 99%
“…3,7 In order to synthesize coatings with a specific chemical functionality, which were previously referred to as "selective functional plasma polymer coatings", multiple studies have employed a modification step after plasma polymer deposition. 2 This can be useful for certain applications like biosensors or antibacterial coatings. Friedrich et al, for example, developed a twostep method that was based on the deposition of bromine-based plasma polymer coatings, after which diamines, diols, dithiols or sodium azides can react with the C-Br bond to form coatings with a high density of amine, alcohol, thiol and azide functionalities, respectively.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation